1982
DOI: 10.1002/ddr.430020207
|View full text |Cite
|
Sign up to set email alerts
|

Naloxone‐induced reversal of clonidine, but not hydralazine, hypotension

Abstract: Bennett, D.A., J.J. DeFeo, E.E. Elko, and L. Harbans: Naloxone reversal of clonidine, but not hydralazine, hypotension. Drug Dev. Res. 2175Res. -179, 1982 Normotensive rats of the Sprague-Dawley strain were administered either the centrally acting hypotensive drug clonidine (0.16 mglkg IP) or the peripherally acting hypotensive drug hydralazine (1.25 rnglkg IP) to induce reliable hypotension (blood pressure reductions of 60-90 mm Hg), as measured by a tail cuff procedure. The opiate antagonist, naloxone (10-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
1

Year Published

1984
1984
1989
1989

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 10 publications
1
6
1
Order By: Relevance
“…These authors questioned whether Wistar Kyoto normotensive controls. However Bennett, Defeo, Elko and La1 (1982) were able to show that naloxone antagonised clonidine-induced the study of Farsang and Kunos (1979) differed from the present experiments, since unanaesthetised animals were used and were given alpha-methyldopa intraperitoneally.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…These authors questioned whether Wistar Kyoto normotensive controls. However Bennett, Defeo, Elko and La1 (1982) were able to show that naloxone antagonised clonidine-induced the study of Farsang and Kunos (1979) differed from the present experiments, since unanaesthetised animals were used and were given alpha-methyldopa intraperitoneally.…”
Section: Discussioncontrasting
confidence: 78%
“…However Bennett, Defeo, Elko and La1 (1982) were able to show that naloxone antagonised clonidine-induced hypotension in normotensive Sprague-Dawley and Long-Evans rats. These authors questioned whether Wistar Kyoto normotensive controls.…”
Section: Discussionmentioning
confidence: 96%
“…This has suggested that, while the nalsxone-resistent component of the effect of clonidine is generally present, the appearance of an additional, opioid-mediated component may be related to the hypertensive process (Ramirez-Gonzalez et al 1983). However, several other reports have demonstrated naloxone antagonism of the effects of clonidine and a-methylnoradrenaline in various strains of normotensive rats other than WKY (Bennett et al 1982;Hamilton and Longman 2982;Petty and de Jong 1984;Dixon and Chandra 1985;Mosqueda-Garcia et al 1986), as well as in nornlotensive cats (Williams 19859, goats (Eriksson and Traomisto 1983) and, in some studies, nonnotensive humans (Resnick et al 1980;Gremse et al 1986). Furthermore, naloxone antagonism of some noncardiovascular effects of clonidine, such as analgesia (Tchakarov et al 1985) or growth hormone release (Bramnert and Hokfelt 1984), has also been reported.…”
Section: Introductionmentioning
confidence: 93%
“…A growing number of reports indicates, however, that the clonidine-naloxone interaction is present in normotensive rats other than Wistar Kyoto rats (6,(12)(13)(14)(15), as well as in normotensive animals of other species (16)(17)(18), suggesting that the underlying endorphinergic mechanism may have a role in cardiovascular regulation under normal physiological conditions. According to recent evidence, the clonidineinduced release of a P3-endorphin-like peptide, as well as the action of this opioid on opiate receptors occurs in the brainstem nucleus of the nucleus tractus solitarii (NTS) (6,19).…”
mentioning
confidence: 99%